2017
DOI: 10.1108/srj-10-2015-0150
|View full text |Cite
|
Sign up to set email alerts
|

Arctic petroleum: local CSR perceptions in the Nenets region of Russia

Abstract: Purpose -The purpose of this paper is to identify and discuss perceptions of petroleum-related corporate social responsibility (CSR) among local and regional authorities, local peoples (indigenous and non-indigenous) and representatives of petroleum companies working or living in the Nenets Autonomous Okrug (NAO) in the Russian Arctic. Although the CSR literature comprises a broad spectrum of approaches, an underrepresentation of perspectives from non-business stakeholders has been suggested. The paper seeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The research findings by Loe et al [59] provided evidence of non-homogenous community preferences. They conducted qualitative interviews and found that local needs and expectations regarding CSR contributions from companies differed among local groups and within the same community.…”
Section: Theoretical Contributionsmentioning
confidence: 97%
“…The research findings by Loe et al [59] provided evidence of non-homogenous community preferences. They conducted qualitative interviews and found that local needs and expectations regarding CSR contributions from companies differed among local groups and within the same community.…”
Section: Theoretical Contributionsmentioning
confidence: 97%
“…A fruitful initial step is to investigate existing scholarly activities in classifying responsibility. Existing literature on companies in the Arctic is firstly, environmentally focused (Hennchen, 2015;Loe et al, 2017;Overland et al, 2021), and then secondly, livelihoods focused (Wettstein, 2009;Olawuyi, 2016;McQueen, 2019). This is perhaps not surprising considering the environmentally sensitive context in which the Arctic region exists.…”
Section: Which Companies Are 'Responsible' In the Arctic?mentioning
confidence: 99%
“…In this study, we extended the previous work done by Srikrishna et al (2016) on developing communities around factories through LCSR activities. LCSR primarily focuses on the company’s activities during the year, where the company has located its manufacturing plant (Shaw, 2007; Loe et al , 2017). Artiles’s (2011) cultural-trait theory argues that directors are individuals with specific thoughts, emotions and personality characteristics that influence their behaviours.…”
Section: Literature Reviewmentioning
confidence: 99%